Cholinesterase homozygous genotype as susceptible biomarker of hypertriglyceridaemia for pesticide-exposed agricultural workers - Zhou, Xingfan; Zhang, Min; Wang, Yuqian; Xia, Hailing; Zhu, Lijin; Li, Guangyi; Rong, Li; Dong, Huahuang; Chen, Rui; Tang, Shichuan; Yu, Min (Biomarkers, 2021)
Dyslipidemia is an emerging metabolic disorder among pesticide-exposed agricultural workers, and this study was aimed to explore biomarkers of hypertriglyceridaemia susceptibility. This cross-sectional study recruited 72 pesticide-exposed subjects and 78 non-exposed controls. Lipid profile, cholinesterase activity, and thyroid hormones were analysed with routine assays. Six loci, including rs11206244 and rs2235544 for deiodinase 1, rs12885300 and rs225014 for deiodinase 2, rs1803274 for butyrylcholinesterase, and rs3757869 for acetylcholinesterase were genotyped using an improved multiplex ligation detection reaction technique. Pesticide-exposed subjects showed higher levels of triglyceride than controls (p = 0.009), although there were comparable cholinesterase activity and genotype frequencies of all six loci between pesticide-exposed subjects and controls. Pesticide-exposed subjects with homozygous genotype of cholinesterase had increased triglyceride levels than controls (p < 0.05). The percentage of hypertriglyceridaemia was 28.6% and 8.8% for pesticide-exposed subjects and controls with homozygous butyrylcholinesterase genotype (p = 0.007) and 20.8% and 14.3% with homozygous acetylcholinesterase genotype (p = 0.792), respectively. Multivariate logistic regression analyses found that odds ratio of hypertriglyceridaemia is 21.92 and 4.56 for pesticide-exposed subjects with homozygous genotype of butyrylcholinesterase (p = 0.001) and acetylcholinesterase (p = 0.036), respectively. Cholinesterase homozygous genotype might be a potential susceptible biomarker in screening pesticide-exposed agricultural workers vulnerable to hypertriglyceridaemia.